Eco-edutourism for biodiversity conservation and community empowerment in Bukit Cubung Karst, Kulon Progo, Indonesia - KUNTUM FEBRIYANTININGRUM; RAHMANIA PAMUNGKAS; AHMAD KAMAL SUDRAJAT; MUCHLISA AMALIA ZAHRA; ABRAHAM HUSAIN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Febriyantiningrum K, Pamungkas R, Sudrajat AK, Zahra MA, Husain A. 2026. Eco-edutourism for biodiversity conservation and community empowerment in Bukit Cubung Karst, Kulon Progo, Indonesia. Biodiversitas 27 (6): d270602. https://doi.org/10.13057/biodiv/d270602. Indonesia’s karst landscapes support distinctive biodiversity but remain highly vulnerable to habitat degradation, weak conservation governance, and limited livelihood options for surrounding communities. This study examines how community-based eco-edutourism can link biodiversity conservation and community empowerment in the Bukit Cubung karst area, Kulon Progo, Yogyakarta, using a participatory action research approach. The intervention combined biodiversity inventory (flora and fauna surveys across four microhabitats), ecological literacy training for local participants, and facilitation of community-based tourism governance. Flora sampling across ten 10 m × 10 m plots and transects documented 23 plant species, while fauna surveys recorded 17 non-avian species, yielding Shannon-Wiener diversity values of H’ = 2.71 for flora and H’ = 2.43 for fauna, indicating moderately high ecological heterogeneity in the study site. Ecological literacy among 20 community participants increased from a mean pre-test score of 42.1% to 87.8% in the post-test, reflecting substantial improvements in knowledge of local species and karst ecosystem functions. Program implementation supported the formation of a village eco-edutourism committee, the development of simple visitor management rules, and the use of the biodiversity inventory as interpretive material for guiding and environmental education activities. These findings suggest that eco-edutourism, when grounded in site-specific biodiversity data and participatory learning, can strengthen local ecological knowledge, foster shared responsibility for conservation, and contribute to community empowerment in fragile karst landscapes.